Kebijakan Luar Negeri Jepang terhadap Pemberlakuan Zona Identifikasi Pertahanan Udara Tiongkok - Faustina Tamisari; Dudy Heryadi (Intermestic: Journal of International Studies, 2017)
The Senkaku Islands dispute has become one the most controversial territorial sovereignty dispute in Asia. Japan and China had been disputing the Islands since 1970. The conflict has escalated to higher level on 2013 when China established the Air Defense Identification Zone. Both China and Japan will respond to any measures exercised by each other to defend each legitimacy on Senkaku Islands. This research aims to scrutinize and analyse the response given by Japan in ecnountering China's Air Defense Identification Zone and what policy implemented by Japan.